The IoT and the next revolutions automating the world - Goyal, Dinesh 1976-; Balamurugan, Shanmugam; Peng, Sheng-Lung; Jat, Dharm Singh (IGI Global, 2019)
"This book covers a spectrum of applications of IoT in building smart world, ranging from smart cities, smart agriculture, to smart home"--
Description based on title screen (IGI Global, viewed 07/32/2019)
Keywords: Internet of things; Automatic control